Rationalité, non-rationalité et théorie prospective : un programme de recherche sur la gestion des crises internationales - Harvey, Frank (Études internationales, 1996)
The strength of rational choice theory and the decision models derived from its axiomatic base (e.g., expected utility, game theory, deterrence, etc.) has always depended on the degree to which the theory's underlying assumptions offer at least a close approximation of reality. Proponents of political psychology have compiled what appears to be an impressive body of evidence against the utility of theories derived from these assumptions. Decision-makers, particularly in a time of crisis, are either unwilling or unable to live up to the demands of rationality. Conflicting empirical evidence from rational choice theorists continues to fuel the debate. In the absence of any attempt to identify areas of consensus, theoretical progress on the question of how to effectively manage international crisis mil remain elusive. In the conviction that this ongoing debate has become counterproductive to the development of crisis management theory, the following paper attempts, in part, to identify areas of consensus and to develop an alternative research agenda around Prospect Theory.